Pengenalan dan Pendampingan UMKM Minuman Herbal Berkah Setia Melalui Digital Marketing Berbasis Marketplace Shopee untuk Menunjang Pemasaran dan Peningkatan Penjualan - Wijayanto, Dwi; Okkiyanto, Ariska Heri; Maulani, Cesanur Iswanti; Darmawan, Rivansa Dibya; Qurniawati, Rina Sari (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
UMKM Berkah Setia in Kadirejo Village is one of the potential UMKM in the area. However, these UMKM still use conventional buying and selling systems and endtrust their product to UMKM centers and souvenir centers. Due to limited capabilities, until now this UMKM product has not been widely known because it has utilized digital technology such as the marketplace as a promotional medium and place for buying and selling. In this service acticity, there are the introduction and assistance of the adoption of E-commerce in the form of the Shopee application media for UMKM Berkah Setia herbal drink. It is hoped that knowledge can increase sales for UMKM owners. The aim of this service activity is not only to introduce the UMKM marketplace, but also to assist in the management of the marketplace so that UMKM income experiences an increase in sales activities. The methods used in this service process are discussion, tutorial, mentoring, and aseesment and evaluation methods. The result from this method show that UMKM actors gain knowledge about creating an account, the process when goods are ordered until they reach the buyer, and UMKM actors gain skills in managing their Shopee accounts